2010
DOI: 10.1039/c0pp00031k
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the interaction between Gβγ and tubulin during light-induced cell elongation of Blepharisma japonicum

Abstract: Blepharisma japonicum ciliates display reversible cell elongation in response to lasting bright illumination. This light-induced phenomenon has been ascribed to the active sliding of the cortical microtubules of the ciliate. The detailed intracellular signaling pathway that activates the microtubule network in response to light, resulting in cell elongation, is unknown. We have previously reported that light stimulation initiates sequential molecular events consisting of a decrease in the phosphorylation of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Slides were put in primary diluted antibody (rabbit polyclonal anti-rat RFC and PCFT (1:200) for 2 h at 37°C followed by secondary antibodies as goat anti-rabbit IgG-horseradish peroxidase (1:200)). Presence of antibody at specific site(s) was revealed using freshly prepared 3,3′-diaminobenzene ( 29 ) and H 2 O 2 at room temperature for 3–5 min and counter-staining with haematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…Slides were put in primary diluted antibody (rabbit polyclonal anti-rat RFC and PCFT (1:200) for 2 h at 37°C followed by secondary antibodies as goat anti-rabbit IgG-horseradish peroxidase (1:200)). Presence of antibody at specific site(s) was revealed using freshly prepared 3,3′-diaminobenzene ( 29 ) and H 2 O 2 at room temperature for 3–5 min and counter-staining with haematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…15,17 Our recent study showed that the modification of Blepharisma body length during cellular illumination may be due to changes in Pdc dephosphorylation. 20 The Pdc-mediated behavioural responses initiated by light-activated G-proteins may include the functional coupling of G-protein subunits and tubulin, which subsequently controls microtubule assembly and stability. 20, 21 Because both photokinesis and cellular elongation occur under the same light conditions in our model, it would be of great interest to examine whether similar lightdependent molecular processes are responsible.…”
Section: Introductionmentioning
confidence: 99%